HUBUNGAN KEDISIPLINAN DAN PENGARUH TEMAN SEBAYA DENGAN KENAKALAN REMAJA PADA REMAJA DI SMPS-PSM KOTA BUKITTINGGI - Falerisiska Yunere; Millia Anggraini; Mayang Hartia Ningrum (Universitas Pahlawan Tuanku Tambusai, 2022)
Adolescent Behavior Deviation can also be referred to as juvenile delinquency, is an act that violates norms, rules or laws in society that is carried out at the age of adolescence or the transition during childhood and adulthood. Data from the National Commission for Child Protection released the number of cases of brawl between students in 2011 as many as 341 cases and 95 fatalities. According to data from the Principal through BK Teachers at SMPS-PSM Kota Bukittinggi the number of SMPS-PSM students is 51 students, of the many students on average every month they enter the BK room as many as 4-8 students and 5 out of 10 students are late to school, There are some students who do not make homework until leaving school before returning home. The aim of the study is to determine the relationship between discipline and peer influence with juvenile delinquency in students at SMP-PSM Kota Bukittinggi in 2020. The method used is descriptive analytic with cross sectional design with tools measure the questionnaire. The sampling technique used was total sampling with a sample of 51 people in the study, then processed using the chi-square-test. The results showed that univariate students were not disciplined (45.1%), students with peer influence were (70.6%) and most of the students committed juvenile delinquency (78.4%) and the bivariate results found that there was a relationship between discipline. with juvenile delinquency obtained p value = 0.00 (p <0.05), and there is a relationship between peer influence and juvenile delinquency obtained p value = 0.001 (p <0.005). The conclusion of this study is that there is a relationship between discipline and peer influence with juvenile delinquency in SMP-PSM Kota Bukittinggi in 2020. It is hoped that schools will improve student discipline to reduce juvenile delinquency. For further researchers, it can examine the relationship between self-motivation and juvenile delinquency. Keywords: Discipline, Juvenile Delinquency, Peers